2021
DOI: 10.1039/d1tc01338f
|View full text |Cite
|
Sign up to set email alerts
|

Molten salt assisted synthesis and electromagnetic wave absorption properties of (V1−x−yTixCry)2AlC solid solutions

Abstract: MAX phases solid solutions have attracted considerable attention owing to their unique structure and properties. However, the synthesis of MAX phase solid solution doped with multi-elements at the M-site is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…If one considers the traditional top-down approach for MXene synthesis, i.e., selective etching of a 3D precursor, there are numerous opportunities for future MXene development. The recent addition of (Mo 0.8 Nb 0.2 ) 5 AlC 4 and high-entropy MAX phases , , has opened up avenues for higher-order MAX phases, where theoretical studies could be used for identifying promising candidates for MXene parent materials and reveal whether chemical order or solid solutions can be expected. Here, choice of method for structure predictions is crucial, also including machine learning procedures for more efficient predictions. Such procedures should ideally also consider formation enthalpy as a descriptor for more realistic predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If one considers the traditional top-down approach for MXene synthesis, i.e., selective etching of a 3D precursor, there are numerous opportunities for future MXene development. The recent addition of (Mo 0.8 Nb 0.2 ) 5 AlC 4 and high-entropy MAX phases , , has opened up avenues for higher-order MAX phases, where theoretical studies could be used for identifying promising candidates for MXene parent materials and reveal whether chemical order or solid solutions can be expected. Here, choice of method for structure predictions is crucial, also including machine learning procedures for more efficient predictions. Such procedures should ideally also consider formation enthalpy as a descriptor for more realistic predictions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been progress in the synthesis of MAX phases with more than two metals. ,, , These so-called high-entropy MAX phases, schematically illustrated in Figure i–l, are composed of three to five metals (M′ + M′′ + M′′′ + ...) forming multielement solid solutions across the M layers. Corresponding MXenes have been demonstrated for n = 1, n = 2, n = 3, , and n = 4 .…”
Section: Max Phasesmain Precursor For Mxenesmentioning
confidence: 99%
“…In order to improve the EM wave absorption performance, a series of MAX phases have been designed and synthesized through tuning in chemical compositions and structures. [8] In 2021, Kong's et al [9] found that (V 1-x-y Ti x Cr y ) 2 AlC MAX phase exhibited prominent EM absorption performance when compared with ternary MAX phases (Ti 2 AlC, V 2 AlC, and Cr 2 AlC). Moreover, high entropy (Mo 0.25 Cr 0.25 Ti 0.25 V 0.25 ) 3 AlC 2 MAX phase kept excellent EM wave absorption even after high-temperature oxidation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] In 2021, Kong's et al. [ 9 ] found that (V 1‐x‐y Ti x Cr y ) 2 AlC MAX phase exhibited prominent EM absorption performance when compared with ternary MAX phases (Ti 2 AlC, V 2 AlC, and Cr 2 AlC). Moreover, high entropy (Mo 0.25 Cr 0.25 Ti 0.25 V 0.25 ) 3 AlC 2 MAX phase kept excellent EM wave absorption even after high‐temperature oxidation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Since PbI 2 has the advantage of a defect passivation effect, modulating the distribution and size of the PbI 2 residues can preserve the positive effect. [12][13][14] Wang et al reported ligand modulation that vertically distributes PbI 2 nanosheets between the grain boundaries. [15] Qin et al reported a zwitterion-functionalized SnO 2 substrate that induces rearrangement of the stacking direction and orientation of residual PbI 2 .…”
Section: Introductionmentioning
confidence: 99%